202k views
4 votes
Give your answer in its simplest form.

Give your answer in its simplest form.-example-1
User Shlong
by
5.3k points

2 Answers

5 votes

Answer:

2m⁻²t⁴

Explanation:

Rule:

If aᵇ / aˣ, then aᵇ ⁻ ˣ


(2m^2t^6)/(m^4t^2) = 2 m^(2-4) t^(6-2) = 2m^(-2) t^(4)

User Juandelsur
by
5.2k points
2 votes

Use
(a^n)/(a^m)=a^(n-m).


</p><p>(2m^2t^6)/(m^4t^2)=2m^(2-4)t^(6-2)=\boxed{2m^(-2)t^4}</p><p>

Hope this helps.

User Janzoner
by
5.1k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.